The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/acel.12287
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial effectors of cellular senescence: beyond the free radical theory of aging

Abstract: Cellular senescence is a process that results from a variety of stresses, leading to a state of irreversible growth arrest. Senescent cells accumulate during aging and have been implicated in promoting a variety of age-related diseases. Mitochondrial stress is an effective inducer of cellular senescence, but the mechanisms by which mitochondria regulate permanent cell growth arrest are largely unexplored. Here, we review some of the mitochondrial signaling pathways that participate in establishing cellular sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
255
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 308 publications
(269 citation statements)
references
References 100 publications
7
255
0
7
Order By: Relevance
“…Moreover, recent findings suggest the possibility of induction of SIPS independently of ROS generation (Ziegler et al, 2015). In the present study, we noted the increase of the% of the cells positive for the presence of SA-b-gal, which widely serves as a senescence marker (Fig.…”
Section: Independent Of Oxidative Stress-induced Premature Senescencesupporting
confidence: 76%
“…Moreover, recent findings suggest the possibility of induction of SIPS independently of ROS generation (Ziegler et al, 2015). In the present study, we noted the increase of the% of the cells positive for the presence of SA-b-gal, which widely serves as a senescence marker (Fig.…”
Section: Independent Of Oxidative Stress-induced Premature Senescencesupporting
confidence: 76%
“…Mitochondrial dysfunction can induce cellular senescence (19,35). We have shown that constitutive Sod2 deficiency causes the chronic presence of senescent keratinocytes in the epidermis (19).…”
Section: Significancementioning
confidence: 99%
“…At the cellular level, converging evidence indicates that mitochondrial dysfunction and cellular senescence are interlinked processes (Ziegler, Wiley, & Velarde, 2015). This is well‐illustrated by the finding that complete removal of mitochondria from senescent cells prevents several features of cellular senescence (Correia‐Melo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%